(untitled) (Journal of Partial Differential Equations, 2021)
This paper investigates a reaction-advection-diffusion equation with double free boundaries. The stationary solution of the system is studied by phase plane analysis. Then, the scale logarithm change sequence method is introduced to show the exact heteroclinic of the system with corresponding parameters. Moreover, a complete description of the types of traveling wave solutions is given with different advection term coefficients.